Longitudinal associations between depressive problems, academic performance, and social functioning in adolescent boys and girls - Verboom, Charlotte E; Sijtsema, Jelle J; Verhulst, Frank C; Penninx, Brenda W J H; Ormel, Johan (Developmental psychology, 2014)
Depressive problems and academic performance, social well-being, and social problems in adolescents are strongly associated. However, longitudinal and bidirectional relations between the two remain unclear, as well as the role of gender. Consequently, this study focuses on the relation between depressive problems and three types of functioning in adolescents while testing gender differences. Depressive problems and functioning of 2,230 children were measured with structured questionnaires. The measurements took place biennially over 3 waves, from late childhood into adolescence (age range = 10-18 years). To examine the longitudinal relation between depression and functioning, path analyses with cross-lagged effects were conducted with structural equation modeling. Multigroup analyses were used to test for gender differences, which were only observed for academic performance. Other findings indicated substantial stability in depressive problems and functioning over time and within-wave correlations between depression and the 3 types of functioning. Poor social well-being was predicted by depressive problems but not the other way around. The relation between depressive and social problems was bidirectional, that is, they predicted each other. Finally, depressive problems and academic performance were bidirectionally related as well but only in girls.